Fostering Spiritual Resilience for Sustainable Recovery: The Case of "KoPi Ngaji" in Rural Yogyakarta - Syakir Jamaluddin; Beta Pujangga Mukti; Riduwan (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Existing studies on post-crisis economic recovery tend to privilege technocratic and pragmatic empowerment models, thereby ignoring the role of religion and spirituality in sustainable community development. Addressing this gap, this study examines how “KoPi Ngaji” constructs a holistic model of faith-based community development by integrating spiritual, social, and economic dimensions. Employing a phenomenological approach, data were collected through in-depth interviews with seven respondents, including a program manager and congregants. The findings reveal that “KoPi Ngaji” operates through an integrative Head, Heart, and Hand (3H) framework, which functions as a cohesive empowerment architecture. It facilitates intellectual engagement through Islamic study, entrepreneurship workshops, and dialogical learning; nurtures emotional bonds, inclusive participation, and a shared sense of belonging; translates spiritual and social capital into concrete material and moral support. These three aspects synergize to cultivate spiritual resilience and enable sustainable community recovery. Contribution: This study contributes to affirming that spiritual well-being can be the foundation of social and economic empowerment.